KONSTRUKSI NILAI KEBERSAMAAN DALAM PROSES PRODUKSI DRAMA "MUSIKAL KELUARGA CEMARA": KONSTRUKSI NILAI KEBERSAMAAN DALAM PROSES PRODUKSI DRAMA "MUSICAL KELUARGA CEMARA" - Clarisse Callista Jacob; Agustin Diana Wardaningsih (GETER : Jurnal Seni Drama, Tari dan Musik, 2026)
The value of togetherness is deeply rooted in Indonesian society. Unfortunately, it is increasingly being eroded by the tide of modernization and digitalization. There are various ways to remind people of the importance of togetherness, one of which is through the performing arts, specifically musical theater.  One particularly compelling example of this is the musical "Keluarga Cemara". The production is adapted from the story of the same title in the TV series and film, but has been staged as a musical since 2024.  The production returned in 2025, with 30 performances in a single month. This study aims to analyze the construction of the value of togetherness in the production process of the musical "Keluarga Cemara." It employs a qualitative research approach using the case study method, with primary data sourced from interviews with individuals involved as part of the creative team for the musical "Keluarga Cemara" as well as audience members. The findings reveal that the musical "Keluarga Cemara" conveys a message of togetherness that extends beyond merely being a plot element. The social construction of the value of togetherness occurs through the relationship between creators, the performance itself, and the audience, expressed artistically through elements such as the script, music, choreography, and stage visuals, as well as the audience's experience. This research is expected to be useful for artists, audiences, and the government. Effective collaboration among these three parties is essential so that performing arts are not merely entertainment but also convey positive values.